Analisis Mine Dewatering pada Penambangan Nikel PT Makmur Lestari Primatama Kecamatan Langgikima Kabupaten Konawe Utara Provinsi Sulawesi Tenggara - ma'rief, Al’Faizah; Harwan; Widodo, Sri (CV Insight Publisher, 2023)
The problem that is often faced in mining activities in open pit mines is high rainfall that can hamper mining operations. Mine Dewatering is a handling of mine water problems by removing water that has entered the mining area (by utilizing differences in height and gravitational force) through drainage channels to temporary storage ponds (sump). This system is commonly applied for handling runoff from rainwater. The purpose of this study is to find out the volume of water entering the mining front, analyze the ideal sump volume to hold runoff water and analyze the ability and duration of pumping to slice water that is in the sump. The average rainfall obtained from data for 2019-2022 is 81 mm/day. The calculation of planned rainfall is determined using a gumble distribution, the calculation of planned rainfall based on the repeat period over 2 years is 201,658 mm/day. Based on the results of the study, the average rain time was 11.97 hours, rainfall intensity was 6,572 mm/hour, runoff coefficient was 0.9 and the rain catchment area was 692,000 m2. So that the runoff water discharge that enters the sump is 4,093.04 m3/hour, the total volume of water entering the sump is 98,233 m3/day. The ideal sump volume to hold runoff water is 71,813.36 m3. The pumping discharge is 1,841.62 m3/hour, the length of sump drying time with an estimated pumping time of 20 hours/day is 9 days.